Efficient algorithms for sensor detachment in WMSNs. (26th August 2014) - Hung, Li–Ling
Target coverage is an important issue in wireless sensor networks (WSNs). This work copes with the target coverage problem which detaches a set of mobile sensors to targets efficiently. Given a set of disconnected targets with different quality of monitoring (QoM) and a set of mobile sensors which are distributed randomly in the networks, this paper develops two efficient algorithms for detaching mobile sensors to the targets such that the QoM of each target is satisfied. Performance study reveals that the proposed mechanisms outperform known mechanisms in terms of the satisfied QoMs of all targets and the movement cost of all mobile sensors as well as the life time of the wireless mobile sensor networks (WMSNs).